Curved characteristics best suited for Growth rates, Relative strength and Performance Time of female Olympic weightlifters - Khaled Ebada (Türk Spor ve Egzersiz Dergisi)
This study aims to identify Growth rates, Relative strength, and performance time for female lifters and defining Curved characteristics best suited for growth rates, relative strength, and performance Time of female Olympic weightlifters and evaluate the performance of snatch and Clean amp; Jerk for female lifters, coaches use the curved characteristics as standard guide them through planning and preparing training programs. The study Applied on a sample of 88 female lifter participants in weightlifting competitions at the 2012 Summer Olympics in London, Where the average age of 25.61± 3.68 years, length 160.18 ± 6.27 cm, weight 67.04 ± 14.33 kg and BMI 25.78 ± 3.99 kg./m2. Were analyzed video film, which was filmed for female lifters knowledge of the technical Committee of the International weightlifting Federation during the Olympic Games in London 2012. The movie was filmed with a video camera at 25 frames/second that is an attempt to analyze the best female lifters to determine for the performance time phases Snatch and Clean amp; Jerk and using the program Kinovea Version 0.8.15 of kinetic analysis. It was found the rate of BMI and the relative strength of female lifters. The results showed final curved characteristics best suited for growth rates, relative strength, results lifts and performance time phases of female Olympic weightlifters, and determine the standard to assess the performance of Snatch and Clean amp; Jerk in weightlifting. These results must be taken into account by the coaches and female lifters to use the standard guide them through planning, preparing weightlifting training programs and to evaluate the performance of snatch and Clean amp; Jerk lifts for female lifters. Modified the weight categories for female weightlifters beginning of 63 kg weight for the following class of 2-3kg until the distinction between the different weight categories results in female lifters, which can achieve for new Olympic  Records in female weightlifting competitions.